Recent advances in diagnostic bronchoscopy - Ong, Philip G.; Debiane, Labib G.; Casal, Roberto F. (Journal of Thoracic Disease, 2016)
The field of diagnostic bronchoscopy has been revolutionized in the last decade primarily with the advent of endobronchial ultrasound (EBUS) but also with the addition of multiple different techniques for “guided-bronchoscopy”. These advances have had a substantial impact in the management of lung cancer with bronchoscopy now providing both diagnosis and mediastinal staging in a single procedure. EBUS has, in fact, become the first choice for staging of the mediastinum over cervical mediastinoscopy (CM). Although EBUS is now a well-established technique, there are continuous efforts from the scientific community to improve its diagnostic performance, and these will be reviewed in this manuscript. The term “guided-bronchoscopy” was recently coined to describe a myriad of techniques that guide our bronchoscopes or bronchoscopic tools into the periphery of the lungs in addition to our conventional fluoroscopy. Electromagnetic and non-electromagnetic navigation, thin and ultrathin scopes, as well as radial-probe EBUS have collectively increased our yield for smaller peripheral lung lesions and continue to evolve. Despite this improved diagnostic yield, there is still ample room for improvement and newer techniques are under way. With new therapies available for patients with interstitial lung disease, achieving a specific histologic diagnosis is now of paramount importance. Given the high morbidity and mortality of surgical biopsies, bronchoscopic cryobiopsy is being rapidly adopted as a safer and effective alternative, and it is likely going to play a major role in the management of these diseases in the near future. This manuscript we will focus on recent advances in EBUS, guided-bronchoscopy, and the use of cryobiopsy.